Carnitine supplementation in sport - Febbraio, V.; Contrò, V.; Proia, P. (European Journal of Sport Studies, 2013)
Carnitine is a compound that can be either endogenous, synthesized by the liver and kidneys, both exogenous, introduced with the diet, in particular through meat and dairy products. Carnitine has a dual role as it is required for long-chain fatty acid oxidation, and also shuttles accumulated acyl groups out of the mitochondria. Muscle requires optimization of both of these metabolic processes during peak exercise performance. Theoretically, carnitine availability may become limiting for either fatty acid oxidation or the removal of acyl-CoAs during exercise. Despite the theoretical basis that carnitine supplementation improves performance of exercise, clinical data have not shown significant benefits in this regard in healthy subjects, nor for strength performance, nor for endurance performance.